2001
DOI: 10.1366/0003702011953199
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Document Papers by Infrared Spectroscopy and Multivariate Statistical Techniques

Abstract: Infrared (IR) spectra of different varieties of document papers were collected with the use of attenuated total reflectance (ATR, 4000-650 cm−1, eight paper varieties) and diffuse reflectance (DRIFTS, 9000-2500 cm−1, six paper varieties) techniques. The spectral data were classified by the application of soft independent modeling of class analogies (SIMCA), using principal components analysis (PCA) to estimate the distance of separation between the different classes of paper samples and discriminant analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…A number of techniques have been proposed to carry out such investigations, among which X-ray diffraction [1][2][3][4], elemental analysis [5,6], IR spectroscopy [7][8][9], Raman spectroscopy [10], image analysis [11] and pyrolysis gas chromatography [12]. Physical testing, such as the measurement of density or of mechanical performance, are less viable since they require special apparatus and imply destructive tests.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of techniques have been proposed to carry out such investigations, among which X-ray diffraction [1][2][3][4], elemental analysis [5,6], IR spectroscopy [7][8][9], Raman spectroscopy [10], image analysis [11] and pyrolysis gas chromatography [12]. Physical testing, such as the measurement of density or of mechanical performance, are less viable since they require special apparatus and imply destructive tests.…”
Section: Introductionmentioning
confidence: 99%
“…with the possibility of examining the sheet's surface. Kher et al [8,9] emphasized that IR spectroscopy, coupled with multivariate statistical methods of analysis, is a powerful discriminating tool for the forensic questioned document examiner. They in fact demonstrated that all the samples in a set of six paper varieties could be differentiated by diffuse reflectance (DRIFTS) and 67.86% of the possible pairs within a population of 8 types of paper could be discriminated by ATR [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear discriminant analysis (LDA) has been used quite frequently in forensic classification task [2][3][4]. However, one of the most popular analytical methods in forensic analysis, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas derivatives have the capability to remove baseline effects and any offset differences between the data [10]. Pre-processing techniques were rarely applied in forensic studies involving instrumental techniques [11][12][13], except normalization, standardization [14][15] and derivatives [16][17]. In fact, the importance and benefits of preprocessing techniques should not be ignored by forensic scientists.…”
Section: Introductionmentioning
confidence: 99%